PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 1 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Maisha Muhti Nr; Farel Olva Zuve (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to describe the effect of the Student Team Achievement Division (STAD) type cooperative learning model on the biography text writing skills of class X SMA Negeri 1 Pancung Soal students. This type of research is quantitative research with experimental method. The design of this research is Posttest Only Control Group Design. The population in this study were class X students of SMA Negeri 1 Pancung Soal totaling 367 people. The sample was determined using purposive sampling technique consisting of control and experimental classes, namely class X Phase E.11 as a control class with 33 people. Class X Phase E.9 as an experimental class totaling 33 people. Based on the t-test results, it is concluded that the Student Team Achievement Division (STAD) type cooperative learning model has an effect on the biography text writing skills of class X students of SMA Negeri 1 Pancung Soal because the t-table value <count (1.79<4.47). So, it can be concluded that the cooperative learning model of Student Team Achievement Division (STAD) type can be used as an alternative in learning to write biography texts of grade X students of SMA Negeri 1 Pancung Soal.